2016
DOI: 10.1080/19768354.2016.1257510
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Korea Red Ginseng extract on 1-methyl-4-phenylpyridinium-induced apoptosis in PC12 Cells

Abstract: Background: Korean Red Ginseng (KRG) is a valuable herb in Asian countries that is used as a crude substance to inhibit inflammation and to enhance vitality, longevity and immunity. The protective effects of KRG against the toxicity of 1-methyl-4-phenylpyridinium (MPP+) were investigated in vitro in the present study. Methods: PC12 cells were pretreated with the water extract of KRG for 24 h, then incubated with MPP+ for 24 h. The growth of the cells was assessed using a live cell viability assay, the ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A separate study done by the same group reported that Korean red ginseng also alleviated the protein expression profile in the substantia nigra that involved in the neuronal development and energy metabolism for the neuronal survival as well as neuroprotection [148]. Meanwhile, in the cellular model, Korean red ginseng treatment inhibited 1-methyl-4-phenylpyridinium ion-(MPP + -) induced apoptosis on rat pheochromocytoma (PC12) cells by preventing the decrease of cell viability and apoptosis and decreasing mRNA expressions of caspase-3 and caspase-9 [149]. Furthermore, this group also reported that Korean red ginseng treatment alleviated behavioral dysfunction induced by MPTP and enhanced differentiation and proliferation of endogenous neural stem cells in the subventricular zone of MPTP-induced mice [150].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…A separate study done by the same group reported that Korean red ginseng also alleviated the protein expression profile in the substantia nigra that involved in the neuronal development and energy metabolism for the neuronal survival as well as neuroprotection [148]. Meanwhile, in the cellular model, Korean red ginseng treatment inhibited 1-methyl-4-phenylpyridinium ion-(MPP + -) induced apoptosis on rat pheochromocytoma (PC12) cells by preventing the decrease of cell viability and apoptosis and decreasing mRNA expressions of caspase-3 and caspase-9 [149]. Furthermore, this group also reported that Korean red ginseng treatment alleviated behavioral dysfunction induced by MPTP and enhanced differentiation and proliferation of endogenous neural stem cells in the subventricular zone of MPTP-induced mice [150].…”
Section: Ginseng Ginseng Is a Perennial Herb Belonging To Thementioning
confidence: 99%
“…In Parkinson’s animal model (pole test), Korean red ginseng, a perennial herb, could enhance the behavioral impairment of mice and prevent dopaminergic neuronal demise and apoptosis in an MPTP-induced model [ 150 ]. In a cellular model, treatment with Korean red ginseng inhibited apoptosis induced by 1-methyl-4-phenylpyridinium ion- (MPP+) on PC12 cells of rat by impeding the cell viability decline and apoptosis via decrease of mRNA expressions of caspase-3 and -9 [ 151 ]. Shim et al showed that Uncaria rhynchophylla reduced ROS production and neuronal cell demise as well as prevented the caspase-3 activity in 6-OHDA-induced toxicity (PC12 cells) [ 152 ].…”
Section: Nutraceuticals In Nds: Multi-targeted Avenuementioning
confidence: 99%
“…Korean Red Ginseng (KRG) is steamed and dried for lengthy preservation, which results in conversion of some of the chemical profiles of ginsenosides [6] . Previous studies have shown that ginseng and KRG suppressed 1-methyl-4-phenylpyridinium-induced cell death in PC12 [7] , [8] and SH-SY5Y [9] cells, and that oral administration of KRG extract protected dopaminergic cell death in the nigrostriatal pathway from MPTP toxicity [10] , [11] and improved cognitive functions in patients with Alzheimer's disease [12] . Moreover, ginsenoside Rg1 attenuated MPTP-induced behavioral impairment and dopaminergic neuronal death through the Wnt/β-catenin signaling pathway [13] and by reducing neuroinflammation [14] , whereas the ginsenoside Rd prevented 1-methyl-4-phenylpyridium-induced cell death in SH-SY5Y cells [15] , and ginsenoside Rb1 suppressed α-synuclein aggregation and toxicity [16] , indicating that KRG has the potential to alleviate PD symptoms; however, the mechanism is not fully understood.…”
Section: Introductionmentioning
confidence: 96%